Corrosion inhibitor performance with presence of FeCO3 film in Co2 corrosion environment under fluid flow effect - Yaakob, S.M. (2013)
Corrosion due to carbon dioxide (CO2) has a major impact on the oil and gas industry by severely affecting production and process facilities. One of the most economic methods to prevent the corrosion of piping and plants is the application of corrosion inhibitors. The presences of corrosion product such as iron carbonate (FeCO3) film may affect to the performance of corrosion inhibitor. In addition to that, fluid flow effect in pipeline may also influence the performance of corrosion inhibitor. Thus, the present work is conducted to study the effect of FeCO3 film to the performance of imidazoline based corrosion inhibitor under fluid flow effect. The experiments were done in glass cells at 80Â°C. The hydrodynamic condition experiment was simulated using rotating cylinder electrode (RCE). Corrosion inhibitor was added at two different concentrations in the iron carbonate film formation. A corrosion rates were measured by linear polarization resistance (LPR) method. The film was later analyzed using scanning electron microscopy (SEM). It was found that a better corrosion protection is still offered by corrosion inhibitor even with presence of FeCO3 film. A synergistic effect is offered by these two films of corrosion inhibitor and FeCO in reducing corrosion rate. Â© (2013) Trans Tech Publications, Switzerland.